2016
DOI: 10.1063/1.4941049
|View full text |Cite
|
Sign up to set email alerts
|

Shock induced phase transition of water: Molecular dynamics investigation

Abstract: Molecular dynamics simulations were carried out using numerous force potentials to investigate the shock induced phenomenon of pure bulk liquid water. Partial phase transition was observed at single shock velocity of 4.0 km/s without requirement of any external nucleators. Change in thermodynamic variables along with radial distribution function plots and spectral analysis revealed for the first time in the literature, within the context of molecular dynamic simulations, the thermodynamic pathway leading to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…In order to carry out simulations with larger timescales, MSST algorithm (multiscale shock technique 47 which is implemented under the LAMMPS 46 framework and has been tested for simulating a unidirectional planar shock propagation for various class of materials 48 51 with sufficient accuracy) has been used to perform simulations up to 10 ns after the passage of shock. The necessary sample details have been given in the Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…In order to carry out simulations with larger timescales, MSST algorithm (multiscale shock technique 47 which is implemented under the LAMMPS 46 framework and has been tested for simulating a unidirectional planar shock propagation for various class of materials 48 51 with sufficient accuracy) has been used to perform simulations up to 10 ns after the passage of shock. The necessary sample details have been given in the Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Velocity autocorrelation of oxygen atoms is presented in figure 3 for the shock-equilibrated water samples at 2.5 normalkm normals1 and 4 normalkm normals1 shock velocities, along with that of normal water (at 1 bar pressure and 300 K) and ice VII crystal structures (at 300 K and 10 GPa). It has been previously reported [14] that water samples shock equilibrated at 2.5 normalkm normals1 and 4 normalkm normals1 represent structures of superheated water and ice VII, respectively. It should be realized that shock compression eventually results in increases in both pressure and temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of ice VII at different temperature and pressure ranges have also been probed in literature using NMR and XRD/Rietveld studies [30–34]. Molecular dynamic studies demonstrating formation of this eight-coordinated ice VII structure [14] also demonstrate a close match with experimentally observed XRD peaks and/or structure factors. Even though XRD studies can provide a good estimation of the crystal structure, they are unable to probe the hydrogen-bond dynamics of the water molecules.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, this limit leads to a certain decrease in shock wave velocity. A. Neogi et al found that within a certain range of shock wave velocities (2.5–3.5 km/s) the temperature generated by the thermal disturbance is reduced in liquid water as shock wave velocities decrease. The shock wave generates an approximately 570 K temperature by thermal disturbance at atmospheric pressure .…”
mentioning
confidence: 99%